Understanding and Exercise of Gluteus Medius Weakness: A Systematic Review - Seung-min Baik; Heon-seock Cynn; Seok-hyun Kim (Korean Research Society of Physical Therapy, 2021)
A weak or dysfunctional gluteus medius (Gmed) is related to several pathologies, and individuals with hip abductor weakness have Gmed weakness. This study aimed to systematically review the literature associated with the anatomy and function of the Gmed, and the prevalence, pathology, and exercise of Gmed weakness. Papers published between 2010 and 2020 were retrieved from MEDLINE, Google Academic Search, and Research Information Sharing Service. The database search used the following terms: (glut* OR medius OR hip abduct*) AND weak*. The Gmed plays an important role in several functional activities as a primary hip abductor by providing pelvic stabilization and controlling hip adduction and internal rotation. Weakness of the Gmed is associated with many disorders including balance deficit, gait and running disorders, femoroacetabular impingement, snapping hip, gluteal tendinopathy, patellofemoral pain syndrome, osteoarthritis, iliotibial band syndrome, anterior cruciate ligament injury, ankle joint injuries, low back pain, stroke, and nocturia. Overuse of the tensor fasciae latae (TFL) as a hip abductor due to Gmed weakness can also cause several pathologies such as pain in the lower back and hip and degenerative hip joint pathology, which are associated with dominant TFL. Similarly, lateral instability and impaired movements such as lumbar spine lateral flexion or lateral tilt of the pelvis can occur due to compensatory activation of the quadratus lumborum for a weakened Gmed while exercising. Therefore, the related activation of synergistic muscles or compensatory movement should be considered when prescribing Gmed strengthening exercises.